Two distinct types of depolarizing afterpotentials are differentially expressed in stellate and pyramidal‐like neurons of entorhinal‐cortex layer II. Issue 3 (5th October 2015) - Alessi, Camilla; Raspanti, Alessandra; Magistretti, Jacopo
ABSTRACT: Two types of principal neurons, stellate cells and pyramidal‐like cells, are found in medial entorhinal‐cortex (mEC) layer II, and are believed to represent two distinct channels of information processing and transmission in the entorhinal cortex–hippocampus network. In this study, we found that depolarizing afterpotentials (DAPs) that follow single action potentials (APs) evoked from various levels of holding membrane voltage ( V h ) show distinct properties in the two cells types. In both, an evident DAP followed the AP at near‐threshold V h levels, and was accompanied by an enhancement of excitability and spike‐timing precision. This DAP was sensitive to voltage‐gated Na + ‐channel block with TTx, but not to partial removal of extracellular Ca 2+ . Application of 5‐μM anandamide, which inhibited the resurgent and persistent Na + ‐current components in a relatively selective way, significantly reduced the amplitude of this particular DAP while exerting poor effects on the foregoing AP. In the presence of background hyperpolarization, DAPs showed an opposite behavior in the two cell types, as in stellate cells they became even more prominent, whereas in pyramidal‐like cells their amplitude was markedly reduced. The DAP observed in stellate cells under this condition was strongly inhibited by partial extracellular‐Ca 2+ removal, and was sensitive to the low‐voltage‐activated Ca 2+ ‐channel blocker, NNC55‐0396. This Ca 2+ dependence was not observed in the residual DAP evoked in pyramidal‐like cells from likewise negative V h levels. These results demonstrate that two distinct mechanism of DAP generation operate in mEC layer‐II neurons, one Na + ‐dependent and active at near‐threshold V h levels in both stellate and‐pyramidal‐like cells, the other Ca 2+ ‐dependent and only expressed by stellate cells in the presence of background membrane hyperpolarization. © 2015 Wiley Periodicals, Inc.